Long-term N fertilization and conservation tillage practices conserve surface but not profile SOC stocks under semi-arid irrigated corn - Stewart, Catherine E.; Halvorson, Ardell D.; Delgado, Jorge A. (Soil & tillage research, 2017)
•SOC was lost over the study through the 0–120cm profile regardless of N fertilizer or tillage treatments.•Fertilization increased surface SOC stocks and reduced SOC loss in the 7.5–15 and 15–30cm depths.•Strip till completely reversed no-till surface SOC gain after the initial 5 years of NT. No tillage (NT) and N fertilization can increase surface soil organic C (SOC) stocks, but these gains are frequently not observed through the soil profile and could be subject to loss through subsequent tillage events. We evaluated a long-term irrigated continuous corn no-tillage (NT) and N rate study near Fort Collins, CO that was split into continuous NT or strip till (ST) treatments after five years. We measured grain and residue yields yearly, and SOC and particulate organic matter C (POM-C) at baseline, 5 yrs and 11yrs later. Continuous NT depressed grain yields (10%) but not stover yields compared to ST. Continuous NT and increasing N fertilization rate increased surface (0–7.5cm) SOC stocks 10 and 13%, respectively, compared to baseline. Seven years of ST completely negated initial surface (0–7.5cm) SOC gain under NT and was only partially explained by POM-C loss (8–25%). All treatments lost between 14 and 19MgCha−1 in the soil profile (0–120cm) compared to baseline with no N or tillage effects. Soil C cycling appears to be rapid in this irrigated system, requiring greater C inputs to maintain SOC stocks. Effective conservation practices will need to balance crop yield, surface erosion protection, and profile-wide SOC stock losses.